Negotiation Identity and Religious Expression in Early Childhood: A Case Study of SDITs in Lombok, Indonesia - Witriani, Witriani; Triantini, Zusiana; Muhrisun, Muhrisun; Emawati, Emawati (Al-Jami'ah Research Centre, 2024)
In recent years, Integrated Islamic Elementary Schools (Sekolah Dasar Islam Terpadu, SDIT) have witnessed significant expansion, particularly in Indonesia’s urban areas. Targeting urban professionals and the upper-middle class, these institutions present a novel educational model that integrates secular and religious instruction. This movement actively disseminates broader Islamic symbols to the public while conducting specific experiments, such as the Islamization of formal education. Notably, several SDITs, classified as elite elementary schools in Lombok, West Nusa Tenggara, exhibit distinct teaching methodologies and incorporate ideological elements that diverge from those commonly found in public elementary schools, which are often perceived as more inclusive. Employing Michel Foucault’s concept of narrative and his framework of power-knowledge as an analytical lens, this study identifies the integration of these schools’ curricula as a significant marker of the emergence of a “new style of Islam” within Indonesia’s educational landscape. This evolving religious paradigm is characterized by an accelerated incorporation of Islamic symbols and the narratives of Post-Reform Islam, including pedagogical approaches that emphasize the teaching of “kaffah” Islam and the cultivation of religious identity from an early age. Educational institutions interpret this transformation favorably, viewing it as an intersection of economic, ideological, and religious opportunities.[Dalam beberapa dekade terakhir, Sekolah Dasar Islam Terpadu (SDIT) telah mengalami perkembangan signifikan, khususnya di kawasan perkotaan Indonesia. Lembaga pendidikan ini menyasar kalangan pekerja urban dan kelas menengah atas dengan menawarkan pendidikan model baru yang mengintegrasikan pendidikan umum dan agama. Gerakan ini secara aktif memperkenalkan simbol-simbol Islam yang lebih luas kepada masyarakat, sekaligus menawarkan pengalaman khas, seperti islamisasi pendidikan formal. Secara khusus, beberapa SDIT yang dikategorikan sebagai sekolah dasar elit di Lombok, Nusa Tenggara Barat, menerapkan metode pengajaran yang unik dengan memasukkan unsur ideologi yang berbeda dibandingkan dengan sekolah dasar negeri, yang sering dianggap lebih inklusif. Dengan menggunakan konsep narasi Michel Foucault serta kerangka kerja power- knowledge sebagai alat analisis, penelitian ini menemukan bahwa integrasi kurikulum di SDIT merupakan salah satu indikator penting dari munculnya “Islam model baru” dalam lanskap pendidikan di Indonesia. Paradigma keagamaan yang berkembang ini ditandai oleh akselerasi penggunaan simbol- simbol Islam serta narasi Islam Pasca-Reformasi, termasuk pendekatan pedagogis yang menekankan pengajaran Islam “kaffah” serta pembentukan identitas keagamaan sejak usia dini. Institusi pendidikan membaca perubahan ini secara positif, melihatnya sebagai peluang ekonomi, ideologi, dan keagamaan yang menguntungkan.]